The clinical efficacy and safety of certolizumab pegol (CZP) in the treatment of rheumatoid arthritis: focus on long-term use, patient considerations and the impact on quality of life - Roy Fleischmann (Dove Medical Press, 2009)
Roy FleischmannMetroplex Clinical Research Center, Dallas, Texas, USAAbstract: Rheumatoid arthritis can cause chronic pain, disability, fatigue and loss of productivity both in the workplace and at home. Fatigue, not joint pain, swelling or that there may be radiographic damage, is frequently mentioned by patients as their most debilitating problem. In the era prior to biologic therapy in rheumatoid arthritis, it was reported that 40% to 50% of individuals reported work loss within 10 years of the onset of their disease. Rheumatoid arthritis is not just associated with chronic pain and inability to function normally; there is a significant economic burden caused by the disease which affects society as well the individual. Work disability in individuals with rheumatoid arthritis occurs early and increases over time. Early, aggressive treatment has now become the norm in clinical practice with changes of medication dictated by measuring the presence of continued disease activity. The combination of adequately dosed methotrexate and a biologic agent, especially a TNFα inhibitor, has been shown to be far more effective than traditional disease modifying anti-rheumatic drugs in early and long-standing disease, with respect to clinical, radiologic and functional outcomes. Unfortunately, not all patients respond to all medications equally; indeed a patient may fail a number of medications, either alone or in combination, and then respond to another medication. For this reason, there is room in our therapeutic armamentarium for additional effective agents such as certolizumab pegol. The results of up to 100 weeks of treatment with certolizumab pegol with an emphasis on functional outcomes, is the focus of this review.Keywords: certolizumab, rheumatoid arthritis, anti-TNF therapy; efficacy, safety, quality of life